2005
DOI: 10.1109/ted.2005.848115
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulations of High-Speed InSb–InAlSb FETs

Abstract: simulations of high-speed InSb-InAlSb FETs.', IEEE transactions on electron devices., 52 (6). pp. 1072-1078. Further information on publisher's website:http://dx.doi.org/10.1109/TED. 2005.848115 Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
10
0
5
Order By: Relevance
“…High-speed devices e.g., InSb FETs operating at room temperature have been successfully fabricated for large gate structures [2]- [4] and Monte Carlo (MC) simulations have indicated that very high speed performance is possible for short gate structures [5]. The unusually high electron drift velocity of InSb results from impact ionization cooling the electrons within the valley and leads to the exceptional high speed potential [5]. In this paper, we explore the possibilities for avalanche photodiode (APD) devices.…”
Section: Self-consistent 2-d Monte Carlo Simulations Of Insb Apd I Imentioning
confidence: 99%
See 1 more Smart Citation
“…High-speed devices e.g., InSb FETs operating at room temperature have been successfully fabricated for large gate structures [2]- [4] and Monte Carlo (MC) simulations have indicated that very high speed performance is possible for short gate structures [5]. The unusually high electron drift velocity of InSb results from impact ionization cooling the electrons within the valley and leads to the exceptional high speed potential [5]. In this paper, we explore the possibilities for avalanche photodiode (APD) devices.…”
Section: Self-consistent 2-d Monte Carlo Simulations Of Insb Apd I Imentioning
confidence: 99%
“…The lower value of S = 3 2 10 estimated from first principles [14] leads to a strong negative differential mobility caused by transfer of electrons to the X valley and a much lower saturated velocity. coefficients and velocity field characteristics for InSb together with details of the simulation techniques have been presented previously [5] and are used unchanged in this paper. For convenience, the ionization coefficients are reproduced in Fig.…”
Section: Self-consistent 2-d Monte Carlo Simulations Of Insb Apd I Imentioning
confidence: 99%
“…It has been proposed elsewhere that this mechanism will cause catastrophic device failure, as the positive feedback drives the device into breakdown. 3 However, there are two limiting factors for this mechanism. Firstly, the reduction in the gate potential means that there is a corresponding increase in hole current that drifts back to the source region.…”
Section: Discussion and Device Modelingmentioning
confidence: 99%
“…Among such materials InSb shows considerable promise because of its extremely high electron mobility and saturation velocity. [1][2][3] The low effective mass and narrow band gap of these materials, however, also introduce a susceptibility to impact ionization-related effects that manifest themselves as an increased output conductance, often referred to as the "kink effect," due to the increase in drain current observable in the output characteristic [4][5][6] giving rise to a conductance kink. Such an effect has been observed in a number of heterostructure systems, with a level of severity that can limit the usefulness of the device.…”
Section: Introductionmentioning
confidence: 99%
“…InAsSb is used in low power, high frequency applications in long-wave and mid-wave infrared region. InAsSb has some advantages over other materials such as its narrow band gap, availability of high quality, low cost substrates, and high electron mobility [5,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%